Method for preparing coal-based carbon material through chemical crosslinking coupling high-temperature carbonization and application of coal-based carbon material
Through chemical cross-linking and coupling high-temperature carbonization method, the structure of coal-based carbon materials is modified, and the problem of low sodium storage performance of coal-based carbon materials in the prior art is solved, achieving more efficient sodium storage performance and electrochemical performance.
Patent Information
- Application Number
- CN202411939603.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, when preparing sodium ion battery anode materials, the sodium storage performance of coal-based carbon materials is low and the structure is uneven, making it difficult to achieve efficient sodium storage.
Chemical crosslinking and coupling high-temperature carbonization method is adopted to introduce groups such as methyl, ethoxy, aldehyde groups into the coal microscope through liquid phase crosslinking to form a bridge bond-fixed aromatic molecular framework structure, inhibit the directional growth of graphite domains, and promote the formation of closed pores.
It improves the sodium storage performance of coal-based hard carbon, achieves greater disorder, layer spacing and number of closed pores, and improves the stability and electrochemical performance of the negative electrode material.
Smart Images

Figure CN119706801A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical energy storage electrode materials, and in particular to a method for preparing coal-based carbon materials by chemical cross-linking coupled with high-temperature carbonization and applications thereof. Background Art
[0002] Lithium-ion batteries (LIBs) and sodium-ion batteries (SIBs) have shown broad application prospects in electric vehicles, smart grids and other fields due to their high energy density, long cycle life, and low self-discharge rate. As one of the most important components in the battery, the anode material has a direct impact on the battery's performance indicators such as energy density, power density, cycle life and safety. Therefore, the design and optimization of the anode material is the key to achieving high performance and low cost of the battery.
[0003] The stable carbon framework and large interlayer spacing of hard carbon make it a promising anode material for sodium-ion / lithium-ion batteries. It usually contains abundant short-range graphite crystallites and long-range amorphous structures, which provide a promising anode material for Li + / Na + Storage provides abundant active sites, and also provides channels for the rapid transfer of electrons. The selection of precursors is crucial for the preparation of hard carbon materials. Coal has become an ideal raw material for preparing negative electrode materials for sodium ion batteries due to its abundant resources, stable samples, low cost, and unique pore structure. However, due to the strong π-π interaction between condensed aromatic hydrocarbon molecules in coal, its carbon layer is easy to melt and stack, and after carbonization, it is converted into soft carbon with low sodium storage capacity. In addition, due to the complexity of the molecular structure and composition of coal, there are still many challenges in the refined preparation of coal-based carbon materials used in sodium ion battery systems. Recently, CN117401669A discloses a coal-based hard carbon material and its preparation method and application, which extracts the vitrinite in coal by physical fine sorting method, and adjusts its microstructure in combination with appropriate pre-oxidation method to enhance its sodium storage performance. However, in the traditional air oxidation process, the reaction speed is fast when oxygen attacks free carbon, which is easily affected by diffusion, resulting in uneven oxidation degree of the sample and the presence of skin-core structure. CN115784196B discloses a sodium ion battery coal-based carbon negative electrode active material, which is mixed with coal by a combined treatment agent of ammonium salt and transition metal salt, and is first calcined at 200-400°C, and then second calcined at 900-1500°C, to prepare a high-performance sodium ion battery negative electrode material. However, this process introduces closed pores into the hard carbon and also preforms a large number of open pores, which is not conducive to the improvement of the first effect. Summary of the invention
[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing coal-based carbon materials by chemical cross-linking coupled with high-temperature carbonization and its application. The preparation method aims to introduce methyl, ethoxy, aldehyde and other groups into the coal microcomponent precursor through liquid phase cross-linking treatment, and anchor them on the condensed ring aromatic hydrocarbon structure to form bridging bonds to fix the aromatic hydrocarbon molecular skeleton structure, successfully inhibit the directional growth of graphite domains during the carbonization process, promote the formation of closed pores, and enhance the sodium storage performance of coal-based hard carbon.
[0005] To achieve the above object, the technical solution of the present invention is as follows:
[0006] The present invention provides a method for preparing a coal-based carbon material by chemical cross-linking coupled with high-temperature carbonization, comprising the following steps:
[0007] Step 1: crushing and screening the raw coal to obtain coal powder with a particle size of ≤75μm;
[0008] Step 2: Deashing, filtering, washing with water until the coal powder is neutral, and drying to obtain an ultra-pure coal sample;
[0009] Step 3: dissolving the ultrapure coal sample in 1,2-dichloroethane solution, adding a cross-linking agent and a catalyst, performing a reflux reaction, and centrifuging to obtain an intermediate product;
[0010] Step 4: subjecting the intermediate product to Soxhlet extraction and drying to obtain modified coal-based microscopic components;
[0011] Step 5: Carbonizing and ball-milling the modified coal-based microscopic components to obtain the coal-based carbon material.
[0012] Preferably, the raw coal in step 1 is at least one of lignite, bituminous coal and anthracite.
[0013] Preferably, in step 3, the crosslinking agent is one or more of diethylene glycol monoethyl ether, phthalic anhydride, terephthalic alcohol, formaldehyde, benzaldehyde, chloroform, dichloromethane, 2,2-diethoxyethanol, phthalic anhydride or diethoxymethane; and the catalyst is ferric chloride or anhydrous aluminum chloride.
[0014] Preferably, in step 3, the mass ratio of the ultrapure coal sample to the cross-linking agent is 1:5-5:1, and the mass ratio of the catalyst to the cross-linking agent is 1:1-1:5.
[0015] Preferably, the temperature of the reflux reaction in step 3 is 60-90° C., the time is 6-24 h, and the centrifugal speed is 1000-10000 rad / min.
[0016] Preferably, the organic solvent used for Soxhlet extraction in step 4 is one or more of methanol, ethanol, acetone or 1,2-dichloroethane.
[0017] Preferably, the carbonization treatment conditions in step 5 are: the atmosphere is nitrogen or argon, the temperature is 800-1500° C., the heating rate is 1-10° C. / min, and the insulation time is 30 min-6 h.
[0018] Preferably, the power of the ball milling in step 5 is 30-100 Hz and the time is 30 min-4 h.
[0019] The present invention also provides the coal-based carbon material as described above with a specific surface area of 2-80 m 2 / g, interlayer spacing greater than 0.37nm, particle size D50 1-10μm, ash content ≤ 0.3wt%, compacted density ≥ 0.85g / cm 3 .
[0020] The present invention also provides the use of the coal-based carbon material as a negative electrode material for a sodium ion battery or a lithium ion battery.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The present invention proposes a method for preparing coal-based carbon materials by coupling liquid-phase organic cross-linking with high-temperature carbonization. Under homogeneous conditions, this strategy causes a series of electrophilic substitution reactions in coal polycyclic aromatic hydrocarbons, introducing additional methyl, ethoxy, aldehyde and other groups into polycyclic aromatic hydrocarbon molecules, and finally forming a hyper-cross-linked structure. The hyper-cross-linked structure has a stable carbon skeleton, which makes it difficult for it to melt and rearrange at high temperatures, and promotes the transformation of coal polycyclic aromatic hydrocarbon molecules from "thermoplastic" to "thermosetting". The prepared derivative hard carbon inherits the carbon skeleton of the hyper-cross-linked polymer, has a larger degree of disorder, interlayer spacing and number of closed pores, and therefore has better sodium storage performance.
[0023] 2. The introduction of additional methyl, ethoxy, aldehyde and other groups into the condensed aromatic hydrocarbon molecules will produce more gas in the subsequent carbonization process, which will help to form a small and disordered carbon structure with a crystallite size, produce more closed pores and ultra-micropores, and achieve in situ uniform activation of the carbon matrix. Combined with subsequent high-temperature carbonization, it will be reorganized into closed pores, which will help the coal-based hard carbon negative electrode to store sodium stably and efficiently.
[0024] 3. The preparation method of the present invention has the advantages of stable raw material source, stable batches, low cost, high carbon yield, dense carbon structure, and simple processing technology, and is easy to realize large-scale preparation of high-performance coal-based carbon materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the TEM image of the coal-based carbon material prepared in Example 1.
[0026] Figure 2 This is the charge and discharge curve of the coal-based carbon material prepared in Example 1.
[0027] Figure 3 This is the rate performance of the coal-based carbon material prepared in Example 1. DETAILED DESCRIPTION
[0028] The present invention is further described below with examples, but the protection scope of the present invention is not limited to the examples. Other changes and modifications made by those skilled in the art without departing from the spirit and protection scope of the present invention are still included in the protection scope of the present invention.
[0029] Example 1
[0030] (1) Put the bituminous coal into a pulverizer for pulverization, and sieve the material through a 200-mesh sieve to obtain coal powder with a particle size of ≤75 μm.
[0031] (2) Take 200 g of sieved coal powder, add it to 800 mL of ethanol solution to fully soak it, and then add 800 mL of deashing solution (the mass ratio of distilled water, 37% HCl, and 40% HF in the deashing solution is 50:30:20). After heating in a 95°C water bath for 4 hours, filter and remove impurities such as inorganic minerals in the coal sample, wash it with water until it is neutral, and dry it to obtain an ultra-pure coal sample.
[0032] (3) Take 10 g of ultrapure coal sample and dissolve it in 375 mL of 1,2-dichloroethane solution, then add 15 g of diethoxymethane and 27.5 g of anhydrous aluminum chloride in sequence, reflux at 80 °C for 24 h, and centrifuge at 8000 rad / min to obtain the intermediate product.
[0033] (4) The intermediate product was washed with methanol and 1,2-dichloroethane in a Soxhlet extractor for 12 h, and then dried in vacuum at 60 °C for 8 h to obtain a modified coal-based maceral.
[0034] (5) The modified coal-based microscopic component sample is placed in a tubular furnace, and in an argon atmosphere, the temperature is raised to 1300°C at a heating rate of 2°C / min, kept at this temperature for 2 hours, and cooled to room temperature; the sample is then transferred to a ball mill, and the ball milling power is 40 Hz and the ball milling time is 2 hours to obtain a coal-based carbon material.
[0035] The specific surface area of the coal-based carbon material prepared in Example 1 is 10 m 2 / g, interlayer spacing greater than 0.385nm, particle size D50 of 2.4μm, ash content of 0.3wt%, compacted density of 0.95g / cm 3. The prepared coal-based carbon material was mixed with carbon black and polyvinylidene fluoride in a mass ratio of 80:10:10 to form a slurry, and then the slurry was evenly scraped onto the current collector aluminum foil. After drying, the electrode was cut. The battery was assembled in a glove box with Ar atmosphere, using metallic sodium as the counter electrode and 1M NaClO4 (the volume ratio of ethylene carbonate to diethyl carbonate is 1:1) solution as the electrolyte to assemble into a CR2032 button cell. After testing, the hard carbon negative electrode has a reversible specific capacity of 348.8mAh / g at a current density of 20mA / g, and a first coulombic efficiency of 90%.
[0036] The above-cut electrode was further used as the working electrode, the lithium sheet as the reference electrode and the counter electrode, and 1MLiPF6 (ethylene carbonate and dimethyl carbonate volume ratio of 3:7) solution was used as the electrolyte, and assembled in a glove box with Ar atmosphere to form a CR2032 button cell. After testing, the hard carbon negative electrode had a reversible specific capacity of 584mAh / g at a current density of 50mA / g and a first coulombic efficiency of 78%.
[0037] Example 2
[0038] The difference between this embodiment and embodiment 1 is that the coal raw material used in step (1) is anthracite. The other steps and parameters are the same as those in embodiment 1.
[0039] The specific surface area of the coal-based carbon material prepared in Example 2 is 4 m 2 / g, interlayer spacing greater than 0.378nm, particle size D50 of 3.5μm, ash content of 0.3wt%, compacted density of 1.01g / cm 3 . The prepared coal-based carbon material was mixed with carbon black and polyvinylidene fluoride in a mass ratio of 80:10:10 to form a slurry, and then the slurry was evenly scraped onto the current collector aluminum foil. After drying, the electrode was cut. The battery was assembled in a glove box with Ar atmosphere, using metallic sodium as the counter electrode and 1M NaClO4 (the volume ratio of ethylene carbonate to diethyl carbonate is 1:1) solution as the electrolyte to assemble into a CR2032 button cell. After testing, the hard carbon negative electrode has a reversible specific capacity of 305.4mAh / g at a current density of 20mA / g, and a first coulombic efficiency of 90%.
[0040] The above-cut electrode was further used as the working electrode, the lithium sheet as the reference electrode and the counter electrode, and 1MLiPF6 (ethylene carbonate and dimethyl carbonate volume ratio of 3:7) solution was used as the electrolyte, and assembled in a glove box with Ar atmosphere to form a CR2032 button cell. After testing, the hard carbon negative electrode had a reversible specific capacity of 454mAh / g at a current density of 50mA / g and a first coulombic efficiency of 68%.
[0041] Example 3
[0042] (1) Place the anthracite into a pulverizer for pulverization, and sieve the material through a 200-mesh sieve to obtain coal powder with a particle size of ≤75 μm.
[0043] (2) Take 200 g of sieved coal powder, add it to 800 mL of ethanol solution to fully soak it, and then add 800 mL of deashing solution (the mass ratio of distilled water, 37% HCl, and 40% HF in the deashing solution is 50:30:20). After heating in a 95°C water bath for 4 hours, filter and remove impurities such as inorganic minerals in the coal sample, wash it with water until it is neutral, and dry it to obtain an ultra-pure coal sample.
[0044] (3) Take 10 g of ultrapure coal sample and dissolve it in 375 mL of 1,2-dichloroethane solution, then add 2 g of phthalic anhydride and 2 g of ferric chloride in sequence, reflux at 90 °C for 6 h, and centrifuge at 8000 rad / min to obtain the intermediate product.
[0045] (4) The intermediate product was washed with ethanol and 1,2-dichloroethane in a Soxhlet extractor for 12 h, and then dried in vacuum at 60 °C for 8 h to obtain a modified coal-based maceral.
[0046] (5) The modified coal-based microscopic component sample is placed in a tubular furnace, and in a nitrogen atmosphere, the temperature is increased to 1300°C at a heating rate of 3°C / min, kept at this temperature for 4 hours, and cooled to room temperature; the sample is then transferred to a ball mill, and the ball milling power is 30 Hz and the ball milling time is 4 hours to obtain a coal-based carbon material.
[0047] The specific surface area of the coal-based carbon material prepared in Example 3 is 10 m 2 / g, interlayer spacing greater than 0.388nm, particle size D50 of 3μm, ash content of 0.3wt%, compacted density of 1.05g / cm 3 . The prepared coal-based carbon material was mixed with carbon black and polyvinylidene fluoride in a mass ratio of 80:10:10 to form a slurry, and then the slurry was evenly scraped onto the current collector aluminum foil. After drying, the electrode was cut. The battery was assembled in a glove box with Ar atmosphere, using metallic sodium as the counter electrode and 1M NaClO4 (the volume ratio of ethylene carbonate to diethyl carbonate is 1:1) solution as the electrolyte to assemble into a CR2032 button cell. After testing, the hard carbon negative electrode has a reversible specific capacity of 330mAh / g at a current density of 20mA / g and a first coulombic efficiency of 87%.
[0048] The above-cut electrode was further used as the working electrode, the lithium sheet as the reference electrode and the counter electrode, and 1MLiPF6 (ethylene carbonate and dimethyl carbonate volume ratio of 3:7) solution was used as the electrolyte, and assembled in a glove box with Ar atmosphere to form a CR2032 button cell. After testing, the hard carbon negative electrode had a reversible specific capacity of 512mAh / g at a current density of 50mA / g and a first coulombic efficiency of 65%.
[0049] Example 4
[0050] (1) Place the lignite into a pulverizer for pulverization, and sieve the material through a 200-mesh sieve to obtain coal powder with a particle size of ≤75 μm.
[0051] (2) Take 200 g of sieved coal powder, add it to 800 mL of ethanol solution to fully soak it, and then add 800 mL of deashing solution (the mass ratio of distilled water, 37% HCl, and 40% HF in the deashing solution is 50:30:20). After heating in a 95°C water bath for 4 hours, filter and remove impurities such as inorganic minerals in the coal sample, wash it with water until it is neutral, and dry it to obtain an ultra-pure coal sample.
[0052] (3) Take 10 g of ultrapure coal sample and dissolve it in 375 mL of 1,2-dichloroethane solution, then add 50 g of diethoxymethane and 10 g of anhydrous aluminum chloride in sequence, reflux at 60 °C for 24, and centrifuge at 10000 rad / min to obtain an intermediate product.
[0053] (4) The intermediate product was washed with ethanol and 1,2-dichloroethane in a Soxhlet extractor for 12 h, and then dried in vacuum at 60 °C for 8 h to obtain a modified coal-based maceral.
[0054] (5) The modified coal-based microscopic component sample is placed in a tubular furnace, and in a helium atmosphere, the temperature is increased to 1300°C at a rate of 1°C / min, kept at this temperature for 3 hours, and cooled to room temperature; the sample is then transferred to a ball mill, and the ball milling power is 100 Hz and the ball milling time is 30 minutes to obtain a coal-based carbon material.
[0055] The specific surface area of the coal-based carbon material prepared in Example 4 is 24 m 2 / g, interlayer spacing greater than 0.384nm, particle size D50 of 2.2μm, ash content of 0.3wt%, compacted density of 0.95g / cm 3 . The prepared coal-based carbon material was mixed with carbon black and polyvinylidene fluoride in a mass ratio of 80:10:10 to form a slurry, and then the slurry was evenly scraped onto the current collector aluminum foil. After drying, the electrode was cut. The battery was assembled in a glove box with Ar atmosphere, using metallic sodium as the counter electrode and 1M NaClO4 (the volume ratio of ethylene carbonate to diethyl carbonate was 1:1) solution as the electrolyte to assemble into a CR2032 button cell. After testing, the hard carbon negative electrode has a reversible specific capacity of 310mAh / g at a current density of 20mA / g and a first coulombic efficiency of 80%.
[0056] The above-cut electrode was further used as the working electrode, the lithium sheet as the reference electrode and the counter electrode, and 1MLiPF6 (ethylene carbonate and dimethyl carbonate volume ratio of 3:7) solution was used as the electrolyte, and assembled in a glove box with Ar atmosphere to form a CR2032 button cell. After testing, the hard carbon negative electrode had a reversible specific capacity of 421mAh / g at a current density of 50mA / g and a first coulombic efficiency of 59%.
[0057] Example 5
[0058] (1) Put the bituminous coal into a pulverizer for pulverization, and sieve the material through a 200-mesh sieve to obtain coal powder with a particle size of ≤75 μm.
[0059] (2) Take 200 g of sieved coal powder, add it to 800 mL of ethanol solution to fully soak it, and then add 800 mL of deashing solution (the mass ratio of distilled water, 37% HCl, and 40% HF in the deashing solution is 50:30:20). After heating in a 95°C water bath for 4 hours, filter and remove impurities such as inorganic minerals in the coal sample, wash it with water until it is neutral, and dry it to obtain an ultra-pure coal sample.
[0060] (3) Take 10 g of ultrapure coal sample and dissolve it in 375 mL of 1,2-dichloroethane solution, then add 10 g of diethoxymethane and 5 g of anhydrous aluminum chloride in sequence, reflux at 80 °C for 12 min, and centrifuge at 6000 rad / min to obtain an intermediate product.
[0061] (4) The intermediate product was washed with methanol and 1,2-dichloroethane in a Soxhlet extractor for 12 h, and then dried in vacuum at 60 °C for 8 h to obtain a modified coal-based maceral.
[0062] (5) The modified coal-based microscopic component sample is placed in a tubular furnace, and in a helium atmosphere, the temperature is increased to 1500°C at a rate of 2°C / min, kept at this temperature for 3 hours, and cooled to room temperature; the sample is then transferred to a ball mill, and the ball milling power is 80 Hz and the ball milling time is 1 minute to obtain a coal-based carbon material.
[0063] The specific surface area of the coal-based carbon material prepared in Example 5 is 6.8 m 2 / g, interlayer spacing greater than 0.381nm, particle size D50 of 5.0μm, ash content of 0.3wt%, compacted density of 0.98g / cm 3. The prepared coal-based carbon material was mixed with carbon black and polyvinylidene fluoride in a mass ratio of 80:10:10 to form a slurry, and then the slurry was evenly scraped onto the current collector aluminum foil. After drying, the electrode was cut. The battery was assembled in a glove box with Ar atmosphere, using metallic sodium as the counter electrode and 1M NaClO4 (the volume ratio of ethylene carbonate to diethyl carbonate is 1:1) solution as the electrolyte to assemble into a CR2032 button cell. After testing, the hard carbon negative electrode has a reversible specific capacity of 315mAh / g at a current density of 20mA / g and a first coulombic efficiency of 90%.
[0064] The above-cut electrode was further used as the working electrode, the lithium sheet as the reference electrode and the counter electrode, and 1MLiPF6 (ethylene carbonate and dimethyl carbonate volume ratio of 3:7) solution was used as the electrolyte, and assembled in a glove box with Ar atmosphere to form a CR2032 button cell. After testing, the hard carbon negative electrode had a reversible specific capacity of 435mAh / g at a current density of 50mA / g and a first coulombic efficiency of 69%.
[0065] Comparative Example 1
[0066] The difference between this comparative example and Example 1 is that no crosslinking agent is added in step (3) of Comparative Example 1. The other steps and parameters of Comparative Example 1 are the same as those of Example 1.
[0067] The coal-based carbon material prepared in Comparative Example 1 was mixed with carbon black and polyvinylidene fluoride in a mass ratio of 80:10:10 to form a slurry, and then the slurry was evenly scraped onto the current collector aluminum foil, and after drying, the electrode was cut. The battery was assembled in a glove box with Ar atmosphere, using metallic sodium as the counter electrode and 1M NaClO4 (the volume ratio of ethylene carbonate to diethyl carbonate was 1:1) solution as the electrolyte to assemble into a CR2032 button cell. After testing, the hard carbon negative electrode had a reversible specific capacity of 100.8mAh / g at a current density of 20mA / g, and a first coulombic efficiency of 44%.
[0068] Comparative Example 2
[0069] The difference between this comparative example and Example 1 is that no catalyst is added in step (3) of Comparative Example 2. The other steps and parameters of Comparative Example 2 are the same as those of Example 1.
[0070] The coal-based carbon material prepared in Comparative Example 2 was mixed with carbon black and polyvinylidene fluoride in a mass ratio of 80:10:10 to form a slurry, and then the slurry was evenly scraped onto the current collector aluminum foil, and after drying, the pole pieces were cut. The battery was assembled in a glove box with Ar atmosphere, using metallic sodium as the counter electrode and 1M NaClO4 (the volume ratio of ethylene carbonate to diethyl carbonate was 1:1) solution as the electrolyte to assemble into a CR2032 button cell. After testing, the hard carbon negative electrode had a reversible specific capacity of 154.5mAh / g at a current density of 20mA / g, and a first coulombic efficiency of 74%.
[0071] Figure 1 This is a SEM image of the coal-based carbon material prepared in Example 1. Figure 1 It can be seen that the carbon material prepared by chemical cross-linking coupled with high temperature carbonization is an aggregate of irregular small particles.
[0072] Figure 2 and Figure 3 The electrochemical properties of the coal-based carbon material prepared in Example 1, including the charge and discharge curves ( Figure 2 ) and rate performance ( Figure 3 ).Depend on Figure 2 and Figure 3 It can be seen that the carbon material prepared by chemical cross-linking coupled with high-temperature carbonization optimization exhibits excellent electrochemical properties. At a current density of 30mA / g, the reversible capacity of the sample is 348.8mAh / g, and the first coulombic efficiency is 90%. At the same time, the coal-based carbon material prepared in Example 1 exhibits excellent rate performance. When the current density is restored to 20mA / g, the reversible capacity also returns to the previous level, indicating that the structure of the hard carbon material prepared is stable.
Claims
1. A method for preparing coal-based carbon materials by chemical cross-linking coupled with high-temperature carbonization, characterized in that: The following steps are involved: Step 1: crushing and screening the raw coal to obtain coal powder with a particle size of ≤75μm; Step 2: Deashing, filtering, washing with water until the coal powder is neutral, and drying to obtain an ultra-pure coal sample; Step 3: dissolving the ultrapure coal sample in 1,2-dichloroethane solution, adding a cross-linking agent and a catalyst, performing a reflux reaction, and centrifuging to obtain an intermediate product; Step 4: subjecting the intermediate product to Soxhlet extraction and drying to obtain modified coal-based microscopic components; Step 5: Carbonizing and ball-milling the modified coal-based microscopic components to obtain the coal-based carbon material.
2. The method for preparing coal-based carbon materials by chemical cross-linking coupled with high-temperature carbonization according to claim 1, characterized in that: The raw coal in step 1 is at least one of lignite, bituminous coal and anthracite.
3. The method for preparing coal-based carbon materials by chemical cross-linking coupled with high-temperature carbonization according to claim 1, characterized in that: In step 3, the crosslinking agent is one or more of diethylene glycol monoethyl ether, phthalic anhydride, terephthalic alcohol, formaldehyde, benzaldehyde, chloroform, dichloromethane, 2,2-diethoxyethanol, phthalic anhydride or diethoxymethane; and the catalyst is ferric chloride or anhydrous aluminum chloride.
4. The method for preparing coal-based carbon materials by chemical cross-linking coupled with high-temperature carbonization according to claim 1, characterized in that: In step 3, the mass ratio of the ultrapure coal sample to the cross-linking agent is 1:5-5:1, and the mass ratio of the catalyst to the cross-linking agent is 1:1-1:
5.
5. The method for preparing coal-based carbon materials by chemical cross-linking coupled with high-temperature carbonization according to claim 1, characterized in that: In step 3, the temperature of the reflux reaction is 60-90° C., the time is 6-24 h, and the centrifugal speed is 1000-10000 rad / min.
6. The method for preparing coal-based carbon materials by chemical cross-linking coupled with high-temperature carbonization according to claim 1, characterized in that: The organic solvent used for Soxhlet extraction in step 4 is one or more of methanol, ethanol, acetone or 1,2-dichloroethane.
7. The method for preparing coal-based carbon materials by chemical cross-linking coupled with high temperature carbonization according to claim 1, characterized in that: The carbonization treatment conditions in step 5 are as follows: the atmosphere is nitrogen or argon, the temperature is 800-1500° C., the heating rate is 1-10° C. / min, and the insulation time is 30 min-6 h.
8. The method for preparing coal-based carbon materials by chemical cross-linking coupled with high temperature carbonization according to claim 1, characterized in that: The power of the ball mill in step 5 is 30-100 Hz, and the time is 30 min-4 h.
9. The coal-based carbon material obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The specific surface area of the coal-based carbon material is 2-80 m 2 / g, interlayer spacing greater than 0.37nm, particle size D50 1-10μm, ash content ≤ 0.3wt%, compacted density ≥ 0.85g / cm 3 .
10. The use of the coal-based carbon material according to claim 9, characterized in that: As negative electrode material for sodium-ion batteries or lithium-ion batteries.
Citation Information
Patent Citations
A coal-based carbon negative electrode active material for sodium ion batteries and its preparation and application
CN115784196B
Cited By
Anthracite-based hard carbon material and preparation method and application thereof
CN122464418A
Anthracite-based hard carbon material and preparation method and application thereof
CN122464418B